From the alien to the alone : a study of soul in Plotinus - Gurtler, Gary M., 1947- (The Catholic University of America Press, 2022)
"A scholarly study of the Neoplatonic philosopher Plotinus (204/5-270) and his understanding of the soul; its chapters include: beauty and the good, forgetting the self, matter as indefinite and incorporeal, omnipresence and incorporeality, and omnipresence and transcendence. The work confirms much recent scholarly consensus on Plotinus, but many of the author's interpretations and general conclusions also give constructive challenges to some existing modes of understanding Plotinus's thought. The arguments and their textual evidence, with the accompanying Greek, provide the reader with direct evidence for testing these conclusions as well as appreciating the nature of Plotinus' philosophizing"--